Modeling ICT usage in business education faculties of tertiary colleges in Nigeria - Isiyaku, Dauda Dansarki; Mohd Ayub, Ahmad Fauzi; Abdul Kadir, Suhaida (Australian Academy of Business and Social Sciences, 2014)
This paper proposes a theoretical model that identifies some key determinants of ICT usage among Business Education faculties in Nigerian tertiary colleges. The methodology of the study is presented in a hypothetical pattern that supposes ICT attitude and subjective norm as independent variables, which determine teachers’ intention to use ICTs in business education classrooms in Nigeria, as well as their eventual involvement in the use of ICTs for their teaching and learning functions. The independent variables (ICT attitude and Subjective Norm) will be measured on the basis of the opinions of respondents on their perceptions of their general dispositions towards using ICTs and how they perceive that most people who are important to them think they should or should not use ICTs in business education classrooms. The limitations of this study are rooted to its preliminary nature, which confines it within the borderlines of integrating what existing literatures reveal. Future research on the subject matter may attempt to underscore the interactions of the aforementioned variables with one another. This study will contribute to knowledge and add to the existing literature on ICT usage. It will be of immense benefit to teachers in Nigerian tertiary colleges and it will play a vital role in filling up the research gap that exist in ICT usage among business education faculties in Nigerian tertiary institutions.